A Systematic Review of Technology-Integrated Focus on Form Instruction in Language Education - Nurfazri, Muhammad; Marinda, Sri Mellia; Husaeni, Nabiel Azhari; Nugraha, Ariska; Solihah, Siti Nuraeni; Sulaeman, Dedi; Ali, Hapid (IKIP Siliwangi, 2026)
This study aims to examine the implementation of digitalized focus-form instruction (FFI) in second language learning and identify the types of technologies supporting its pedagogical functions. Using a systematic literature review (SLR) based on PRISMA guidelines, data were collected from major academic databases for publications from 2021 to 2025: Scopus, ERIC, Taylor & Francis, EBSCO, Wiley Online, Sage, and ScienceDirect. Of the 2,426 identified records, 13 articles met the inclusion criteria and were analyzed. The review results indicate that digital FFI is implemented through three main approaches: explicit, implicit, and hybrid. Besides, this research shows a variety of technologies, including ChatGPT and other large language models, auditory feedback systems in digital literacy games, the Meta AI chatbot via WhatsApp, Grammarly, AI-based diagnostic platforms, Siri as speech recognition, the PRAAT acoustic analysis tool, LLM in the DynaWrite platform, multimedia captioning tools (Nawmal), web-based multimodal teaching platforms, Machina Callida as a corpus-based CALL tool, and ASR-based speech-to-text tools. Thus, these findings highlight the potential of digital FFI to improve linguistic accuracy, noticing, and metalinguistic awareness.